Ultrahigh capacitance of NiCo2O4/CeO2 mixed metal oxide material for supercapacitor applications - Santhosh, G.; Nayaka, G. P.; Bhatt, Aarti S. (Journal of Alloys and Compounds, 2022)
Pertaining to research on energy consumption and energy storage systems, new and efficient mixed metal oxides of NiCo2O4/CeO2 as pseudo-capacitor materials have been successfully prepared by sol-gel combustion method. The synthesized unique spinel nanomaterials have been analyzed for structural and morphological characterization by FT-IR, XRD, XPS and electron microscopy techniques. The mesoporous structure and large specific surface area of the synthesized nanomaterials provide an easy channel for ion mobility rendering an effortless redox process at the electrode electrolyte interface. As a consequence, it is observed that NiCo2O4 mixed with 10% of CeO2 exhibits an excellent specific capacitance of 1355 Fg(-1) at 5 Ag-1 along with a high cycling stability with only 4.7% capacity loss at the end of 6000 cycles at a charge-discharge current density of 10 Ag-1. The results obtained are in par with some of the recent electrode materials used for supercapacitors suggesting the possible employment of NiCo2O4/CeO2 mixed metal oxides in energy storage applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Charge-discharge; cyclic voltammetry; NiCo2O4/CeO2; specific capacitance; supercapacitor